DEVELOPMENT OF STUDENT WORKSHEETS (LKS) BASED LEARNING CYCLE 5E ON MAIN MATERIAL ELASTICITY AND HOOKE’S LAW CLASS X HIGH SCHOOL - KURNIA PUTRI LAHMITA; SARDIANTO MS; APIT FATHUROHMAN (Sriwijaya University Learning and Education International Conference, 2016)
Has successfully developed the student worksheets (LKS) 5E learning cycle based on the subject matter and Hooke's law of elasticity class X SMA valid and practical. The process of developing student worksheet (LKS) through the steps of research development model based product development Rowntree, include: (1) the planning stage of the needs analysis worksheets, requirements analysis learning cycle 5E, analysis of material needs elasticity and Hooke's law (2) stage the development of the formulation of learning objectives, development topics, the drafting, production prototypes, and (3) the evaluation stage. At this stage of the evaluation, researchers used a model formative evaluation Tessmer and tailored to the needs of researchers, namely: (1) self-evaluation; (2) The expert review; (3) one-to-one; and (4) small group. Data collection techniques used in the form walkthrough (validation expert lecturer and teacher of physics), the questionnaire responses of students, and student activity observation. The results of the research development of student worksheet (LKS) showed that the results of the validation stage of expert reviews, the average ratings of 88.20 validator (category very valid), meaning the student worksheet (LKS) product developed by the researchers included in the category of very valid. The results of the questionnaire responses of students at the stage of one-to-one shows the average percentage of 82.37% (practical categories), and at the stage of a small group showed that average percentage of 90.88% (the category of very practical), means the student worksheet (LKS)product had a very practical according to student responses. The average percentage of student activity by 90% (the excellent category), meaning the student worksheet (LKS)product is excellent when used in learning physics. Based on the results of the study concluded that the student work product sheet (LKS) 5E learning cycle based on the subject matter and Hooke's law of elasticity class X SMA developed was valid and practical.